2022
DOI: 10.3390/pr10112437
|View full text |Cite
|
Sign up to set email alerts
|

Purity Control Based on a Type-II Fuzzy Controller for a Simulated Moving Bed

Abstract: The control of a simulated moving bed (SMB) is always a challenging chemical control topic due to its complexity and nonlinearity. Its mathematical model must undergo an affine transformation and digitization before it can be controlled. Basically, there are three aspects that need to be considered in the nonlinear control of an SMB. First, the nonlinear characteristics are more complicated due to the switching time parameters of discrete events. Second, the control objective is not to minimize the control out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Hoon et al employed a data-driven Deep Q Network, a model-free reinforcement learning method, to train a control strategy for SMB processes which approaches optimality [18]. More relevant studies can be found in the references [19][20][21][22][23][24][25]. Although using machine learning and deep learning approaches to treat the SMB system as a black box can help bypass the complexities of the underlying mechanism, this approach may become highly susceptible to disturbances or To control the simulated moving bed process of binaphthol enantiomers separations, Nogueira et al proposed a nominally stable MPC controller, also known as infinite horizon model predictive control (IHMPC) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Hoon et al employed a data-driven Deep Q Network, a model-free reinforcement learning method, to train a control strategy for SMB processes which approaches optimality [18]. More relevant studies can be found in the references [19][20][21][22][23][24][25]. Although using machine learning and deep learning approaches to treat the SMB system as a black box can help bypass the complexities of the underlying mechanism, this approach may become highly susceptible to disturbances or To control the simulated moving bed process of binaphthol enantiomers separations, Nogueira et al proposed a nominally stable MPC controller, also known as infinite horizon model predictive control (IHMPC) [11].…”
Section: Introductionmentioning
confidence: 99%